Legal Privilege Legislation: Consequences for Patient Safety - Robert Robson, Carolyn Canfield, Darrell Horn, Allison Kooijman, Nelly D. Oelke, Sam Sheps, Ryan Sidorchuk and Fiona MacDonald (Healthcare Quarterly, 2022)
Increasing awareness of the extent of preventable harm from healthcare has led to efforts to improve patient safety through a variety of efforts, including legislation. Extending legal privilege to quality and safety reviews leads to further harm for many patients, families and healthcare providers. The intentional isolation, silencing and exclusion after the incident undermines trust, prevents learning and impedes an opportunity to heal and recover for all those directly involved. Our case study examines Section 51 of British Columbia's Evidence Act (1996) and concludes that amending this legislation is an urgent and necessary step toward trauma-informed care.
Keywords: patient harm, trust, accountability, Section 51, adverse healthcare event, trauma informed, medical error, case study